Odontología, nuevas perspectivas por pandemia COVID-19 Revisión Bibliográfica - Pesenti Moreira, Piero; Muñoz Jiménez, Esteban; Campos Cannobio, Valeria (Journal of Oral Research, 2021)
At the end of 2019, a suspicious increase in pneumonia cases occurred in the region of Wuhan, China.